Peliosanthes longiracemosa (Asparagaceae), a new species from limestone areas of northern Vietnam - Nguyen, Khang Sinh; Tanaka, Noriyuki; Averyanov, Leonid V.; Nguyen, Thanh Son; Pham, van The (Phytotaxa, 2021)
Peliosanthes longiracemosa, a new species from limestone areas of northern Vietnam, is described and illustrated. It is most similar to P. macrostegia in having a distally incurved staminal corona and a distinct pyramidal style, but clearly distinguishable chiefly by the broader leaf blades with more longitudinal veins and closer transverse veinlets, relatively longer, more slender raceme, more numerous widely expanded flowers with recurved perianth segments, and more incrassate, depressed globose staminal corona. Information on the habitat and phenology as well as notes on the taxonomic relationships with other congeners is also provided.